1994
DOI: 10.1099/0022-1317-75-8-1943
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of human adenovirus E1a by E3 gene products: evidence for translational control of E1a by E3 14{middle dot}5K and/or E3 10{middle dot}4K products

Abstract: The mechanism for down-regulation of Ela expression by products encoded in the E3 transcription unit of human adenovirus types 2 and 5, that occurs in infected L929 cells, has been investigated further. We show that the phenomenon occurs in different mouse cells and also in some human cells suggesting that the observations have relevance to natural human infections. We also provide evidence that probably all viral proteins are down-regulated by E3 products, although to different extents, but that host proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Side by side comparison of the two CRAds showed that the presence of the entire E3 region was detrimental to CRAd activity, leading us to pursue the experiments with the CRAd lacking the E3 region. The detrimental effect of the entire E3 region was consistent with previous data showing that the E3 products 14.5K and 10.4K down-regulated E1A at the translational level (41). However, more recent evidence indicates that restoration of the E3 adenoviral death protein or even the entire E3 coding region might enhance CRAd activity (42 -44), strongly suggesting that AV22EL lytic activity could be greatly improved by adding the adenoviral death protein coding region without losing tumor specificity.…”
Section: Discussionsupporting
confidence: 80%
“…Side by side comparison of the two CRAds showed that the presence of the entire E3 region was detrimental to CRAd activity, leading us to pursue the experiments with the CRAd lacking the E3 region. The detrimental effect of the entire E3 region was consistent with previous data showing that the E3 products 14.5K and 10.4K down-regulated E1A at the translational level (41). However, more recent evidence indicates that restoration of the E3 adenoviral death protein or even the entire E3 coding region might enhance CRAd activity (42 -44), strongly suggesting that AV22EL lytic activity could be greatly improved by adding the adenoviral death protein coding region without losing tumor specificity.…”
Section: Discussionsupporting
confidence: 80%
“…These results suggest that an E3B-deleted virus may have a growth advantage over the wild-type virus. The presence of the E3B gene complex RID has been reported to negatively affect E1A protein expression 36 and may play a role in the observed CPE phenotype of the E3B-deleted viruses. Further experiments are planned to address this observation more rigorously.…”
Section: Figure 6 Murine Tnf Produced By Onyx-321 Kills Susceptible Cmentioning
confidence: 99%
“…Even for the more extensively characterized HAVs, knowledge of virulence is still rudimentary. Studies to date have largely centered around the involvement of the E3 region of the HAV genome in pathogenicity (11,13,41,44), although this focus does not exclude the possible involvement of other regions of the genome (for example, the E1 region has also been implicated) (13,45).…”
mentioning
confidence: 99%
“…In addition, the 14.7K, 14.5K, and 10.4K proteins are all involved in avoidance of cell lysis by tumor necrosis factor (14,15,20). The E3 14.5K and/or 10.4K products also interact with the E1a region (45) to reduce E1a protein levels, including the immunodominant cytotoxic T-cell antigen. Down regulation of this antigen protected infected cells from cytolysis (27).…”
mentioning
confidence: 99%